RANCANGAN ALAT BANTU KERJA PENYORTIRAN EMBER CAT BERDASARKAN RISIKO MUSCULOSKELETALDISORDERS (MSDs) DI PT.Z MENGGUNAKAN VIRTUAL ENVIRONMENT - Aji Bimo Prasetyo, - (2019)
Heavy-duty work and non-ergonomic design tools result in Musculoskeletal disorder complaints. This problem is found in the production section in the sorting of the paint bucket which is tasked with checking the paint bucket and separating the good and the bad. In accordance with the calculation of work posture using the Rapid Upper Limb Assessment (RULA) method, the Ovako Working Posture Analysis (OWAS) and the Nordic Body Map (NBM) in previous studies. So in this study will provide a solution in the form of a proposal that is suitable for reducing the risk. The research began by collecting Anthropometric data from operators to determine comfortable material handling measurements with the operator's work posture. Then the results of the Material Handling proposal design will be tested for the value of RULA using the Virtual Environment method. The final results of the RULA show that the work posture with the proposed design is more ergonomic